Mulheres feministas: problematizando violências na internet - Romio, Caroline Matos (2023)
The internet has been used to spread violence and hate speech against women, especially when then identify as feminists or promote feminist principles. In this sense, there is an antifeminist countermovement that has appropriated digital spaces for the dissemination of misogynistic and anti-egalitarian ideas, developing sophisticated strategies of violence against women. These strategies are based both on the dissemination of speeches that misinform and contaminate the public debate, and on discourses that aim to intimidate, frighten, harass and abuse feminist women. These forms of violence are presented as everyday elements linked to feminist action and signal that the internet has been configured in a hostile space for women. Considering this scenario and supported by the Theory of Social Representations and feminist theories, this thesis aims to problematize and analyze the dynamics of violence experienced by feminist women in the internet space in Brazil, seeking to identify how the coping strategies and resistance used by feminist women move and (co)produce social representations. Specifically, it aims to: understand how social representations about women legitimize anti-feminist violence on the Brazilian internet; problematize how the defense of expanding women's access to their sexual and reproductive rights make feminists targets of attacks on the internet; to understand what knowledge feminist women produce about the antifeminist movements that operate on the internet. The methodological path for carrying out the thesis used ethnography on the internet, integrating the use of participant observation recorded in a field diary, semi-structured interviews and questionnaires answered by women who define themselves as feminists and act by multiplying feminism on the internet. After analyzing the information, we constructed four studies: “Field Diary: records of antifeminism on the internet”; “The Interviews: the power of whispers to overcome patriarchy”; “Questionnaires: antifeminism, its promoters and the union for resistance”; “Thinking Antifeminism on the Internet: knowledge and meanings about violence against feminist women in Brazil”. With the information obtained, we could see that feminism, by destabilizing what is understood as women's social and cultural attributions, tensioning the notion of reproductive work, causes changes in the gender dynamics. Anti-feminist violence aims at silencing divergent women as it reinforces the unique discourse of patriarchy. This silencing can count on the facilitation of media platforms and State inaction.